2020
DOI: 10.3390/su12187748
|View full text |Cite
|
Sign up to set email alerts
|

Application of Modern Web Technologies to the Citizen Science Project BAYSICS on Climate Research and Science Communication

Abstract: Participatory sensing has become an important element in citizen science projects. Information and communication technologies (ICTs) such as web platforms and mobile phones can generate high-resolution data for science and progress assessment of the United Nations Sustainable Development Goals (e.g., SDGs 11, 13, and 15). This paper gives an overview of web technologies in citizen science and illustrates how these technologies were applied in the citizen science project BAYSICS (Bavarian Citizen Science Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Phenological data especially by observers on the ground and in situ measurements have been collected worldwide, contributing to a series of long-term phenological records for climatic research studies such as trend analysis and validation for remote sensing and imaging (Izquierdo-Verdiguier et al 2018), as well as for pollen and agrometeorology (Chuine et al 2004;Migliavacca et al 2012) and citizen science, since the majority of observers in these networks are volunteers (citizen scientists) (Lehmann et al 2018). Ground observations are valuable since they start from observing responses of individual species, later on sum changing patterns or even (warming) trends from the long-term series, and finally end up with assessing consistency among dominant phenology (Badeck et al 2004). Based on these data, many studies have shown the attributable link from climate variability to phenology, particularly referring to the occurrence dates of earlier (i.e., advanced) flowering and other spring onset phases (e.g., Chmielewski et al 2004;Menzel et al 2020;Rafferty et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Phenological data especially by observers on the ground and in situ measurements have been collected worldwide, contributing to a series of long-term phenological records for climatic research studies such as trend analysis and validation for remote sensing and imaging (Izquierdo-Verdiguier et al 2018), as well as for pollen and agrometeorology (Chuine et al 2004;Migliavacca et al 2012) and citizen science, since the majority of observers in these networks are volunteers (citizen scientists) (Lehmann et al 2018). Ground observations are valuable since they start from observing responses of individual species, later on sum changing patterns or even (warming) trends from the long-term series, and finally end up with assessing consistency among dominant phenology (Badeck et al 2004). Based on these data, many studies have shown the attributable link from climate variability to phenology, particularly referring to the occurrence dates of earlier (i.e., advanced) flowering and other spring onset phases (e.g., Chmielewski et al 2004;Menzel et al 2020;Rafferty et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 2,210,600 observations and 47,100 observers currently exist on iNatualist, with animals being the most commonly observed category (37%), followed by insects (22%), plants (22%), and birds (9%). Social sciences are represented to a slightly lesser extent by projects in the fields of history, humanities, and health [ 13 , 67 ]. A steep increase in the number of observers and observations occurred in 2017.…”
Section: Resultsmentioning
confidence: 99%
“…However, the proportions of international and local projects vary widely among countries. Compared to Mongolia, where the share of local projects is 10%, the share in Germany, for example, is significantly higher at approximately 70% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indicator 1 addresses the use of the well-known online platforms (websites, web apps, and mobile apps) in citizen science projects [31][32][33][34][35]. Traditionally, projects are presented on a website; this is where interested citizens make initial contact with a project and are then directed to a web app.…”
Section: Investigated Web Technologies 251 Online Platformsmentioning
confidence: 99%